Gram-Negative Toe Web Infections - Kelita Waterton; Shari Lipner (Mattioli1885, 2024)
Gram-negative bacterial toe web infection (GNTWI) is a common dermatologic condition affecting the interdigital spaces. The clinical presentation ranges from mild erythema to exudative maceration of the web spaces that may extend to in other areas of the foot and lead to cellulitis in severe cases. Pseudomonas aeruginosa is the most commonly identified etiologic agent. Occlusive and humid environments, pre-existing dermatologic conditions, and fungal infections increase the risk of developing GNTWI. GNTWI has a broad differential diagnosis including erythrasma, tinea pedis, pitted keratolysis, eczematous dermatitis, and malignancies. Diagnosis is performed using bacterial and fungal cultures. There is a lack of a standardized treatment regimen for GNTWI. While GNTWI is fairly common, it may still be under-recognized by dermatologists due to the limited medical literature. This article presents a review of GNTWI, its clinical features, epidemiologic factors, etiologic agents, predisposing factors, diagnostic methods, and therapeutic options.